Favorable Effects on Pulmonary Vascular Hemodynamics with Continuous-Flow Left Ventricular Assist Devices Are Sustained 5 Years After Heart Transplantation. Issue 1 (January 2018) - Saidi, Abdulfattah; Selzman, Craig H.; Ahmadjee, Abdulmohsin; Al-sarie, Mohammad; Snow, Gregory L.; Wever-Pinzon, Omar; Alharethi, Rami; Reid, Bruce; Stehlik, Josef; Kfoury, Abdallah G.; Bader, Feras
Abstract : It is unclear whether pulmonary hemodynamics improvement with left ventricle unloading with left ventricular assist devices (LVADs) is sustained long term after heart transplant (HT). We sought to assess the effects on pulmonary vascular hemodynamics during continuous-flow (CF-LVAD) and pulsatile flow (PF-LVAD) support up to 5 years after HT. Invasive hemodynamics were evaluated before LVAD, before HT, and at 3 months, 1, and 3–5 years posttransplant. Thirty-eight patients were included in the study and divided into two groups according to the type of LVAD support. The two groups were well matched in age and gender. Mean pulmonary artery pressure (PAPm) and systolic PAP (PAPs) improved significantly in the PF-LVAD group (40 ± 10.6 to 19.8 ± 4.4 mm Hg and 62.7 ± 14.9 to 31.8 ± 5.9 mm Hg, respectively) and in the CF-LVAD group (37.4 ± 11.6 to 22.4 ± 7.7 mm Hg and 53.7 ± 18.0 to 34.6 ± 11.8 mm Hg, respectively). Reductions in PAPm and PAPs were more pronounced in PF-LVAD group than in CF-LVAD group ( p = 0.005 and p = 0.03, respectively). After HT, the improvement in PAPm and PAPs was sustained after 3–5 years in patients who received PF-LVAD (22.6 ± 6.5 and 32.2 ± 9.2 mm Hg, respectively) and in patients who received CF-LVAD (22.2 ± 8.4 and 33.8 ± 9.6 mm Hg, respectively). In conclusion, long-term LVAD support resulted in significant improvement in PAPm and PAPs regardless of the pump generation. The improvement in hemodynamics observed during LVAD support was sustained 3–5 years posttransplant.